Multivalent contacts of the Hsp70 Ssb contribute to its architecture on ribosomes and nascent chain interaction - Hanebuth, Marie Anne; Kityk, Roman; Fries, Sandra J.; Jain, Alok; Kriel, Allison; Albanese, Veronique; Frickey, Tancred; Peter, Christine; Mayer, Matthias P.; Frydman, Judith; Deuerling, Elke (Nature Communications, 2016)
The correct folding of proteins often requires the intervention molecular chaperones, which can occur co-translationally. Here the authors identify elements of yeast Ssb (Hsp70) that mediate ribosomal binding, and suggest a mechanism that directs efficient interaction of Ssb with the nascent chain.